Paradigma Kurikulum Merdeka Bagi Guru Sekolah Dasar - Chumi Zahroul Fitriyah; Rizki Putri Wardani (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2022)
Independent curriculum was dream of implementation curriculum after pandemic. It has a several principle, on of them was flexibility. Its means that school can apply this curriculum based on the environment. But, this curriculum was very newby for being implemented by teacher. The objective of this research was describing kurikulum merdeka by conceoptual that would be implemented in 2025 later. The research method used was a descriptive qualitataive. Collecting data used depth interview and literature review from journal about Kurikulum Merdeka. Analyzing data used Miles model, there were three steps, 1) collecting data, 2) verification, and 3) conclusion. Based on the result, this curriculum can be implemented in various regions. The preparation teacher to face of this independent curriculum were join the workshop about this curriculum helds by educational and private institutions. Based on interview with other elemntary school teacher, they gave an enthusiastic response in this curriculum. It hope this curriculum that would be implemented can be gain our goals Indonesian education.